Antibacterial Test and Isolation of Xanthones from Pericarps Mangosteen (Garcinia mangostana L.) using Calcium Oxide (CaO) as a Vacuum Liquid Chromatography (VLC) Stationary Phase - Ni Komang Tri Dharmayani; Inggit Garnasih; Emmy Yuanita; Maria Ulfa; Sudirman Sudirman; Made Ganesh Darmayanti; Maulida Septiyana (The University of Mataram, 2022)
Xanthones are one of the biggest classes of compounds in natural product chemistry. Xanthones have been isolated from pericarp mangosteen (Garcinia mangostana L.) and then purified with VLC using calcium oxide (CaO) as the stationary phase and eluted using n-hexane: EtOAc of increasing polarity. Extraction of the pericarp mangosteen using the maceration method with acetone as the solvent. The isolation of xanthones was carried out through various chromatography techniques, such as vacuum liquid chromatography (VLC), gravitational column chromatography (GCC), and thin layer chromatography (TLC). The molecular structure of the compound was identified based on spectroscopy data, including IR, 1D NMR (1H and 13C), and 2D NMR (HSQC and HMBC). Based on the analysis of spectrum data, the isolated compound is ɑ-mangostin. The acetone extract and ɑ-mangostin were also examined for antibacterial activity against Gram positive (+) Staphylococcus aureus (S. aureus) ATCC 25923 and Gram negative (-) Escherichia coli (E. coli) ATCC 25922. The largest inhibition zone was shown by ɑ-mangostin against S. aureus (12.16 mm) more than E. coli (12 mm).